Effects of Consciousness and Consistency in Manual Control of Visual Stimulus on Reduction of the Flash-Lag Effect for Luminance Change - Ichikawa, Makoto; Masakura, Yuko (Frontiers in Psychology, 2013)
Four experiments investigated how observers’ consciousness about their control of stimulus change affects the visual perception associated with the illusory flash-lag effect. In previous study (Ichikawa and Masakura, 2006), we found that the flash-lag effect in motion is reduced if observers were conscious that they were controlling stimulus movements by the use of computer mouse, even if the stimulus moved automatically, independently of observer’s mouse control. In the other study (Ichikawa and Masakura, 2010a), we found that the consistent directional relationship between the observer’s mouse control and stimulus movement, which is learned in our everyday computer use, is important for the reduction of the flash-lag effect in active observation. In the present study, we examined whether the reduction of the flash-lag effect in active observation requires the observers’ consciousness about their control of stimulus change, and consistency in coupling mouse movement direction and stimulus change across trials in experiments. We used the flash-lag effect in luminance change because there is no intrinsic relationship between observer’s mouse control and luminance change in our everyday computer use. We compared the illusory flash-lag effects for automatic change of the luminance with luminance change that was controlled by the observers’ active manipulation of a computer mouse. Because the flash occurs randomly in time, observers could not anticipate when the flash was presented. Results suggest that the not only observer’s consciousness of controlling the stimulus, but also consistency in coupling mouse movement direction with stimulus change, are required for the reduction of the flash-lag effect in active observation. The basis of the reduction of the flash-lag effect in active observation is discussed.